Peritonitis Rate in Patients Undergoing Automated Peritoneal Dialysis - Anees, Muhammad; Munir, Irfan; Butt, Noman; Elahi, Irfan; Akbar, Hina; Pervaiz, Shahbaz (Pakistan Journal of Kidney Diseases, 2024)
Introduction: Peritonitis is a serious complication causing significant morbidity and mortality nevertheless can be prevented in most cases with careful infection control precautions. The objective of this study was to determine the rate of peritonitis in patients undergoing automated peritoneal dialysis (APD). Study Design: Descriptive retrospective study Place and Duration of Study: Department of Nephrology, Mayo Hospital Lahore, from February 2023 to February 2024. Methods: Twelve patients started on automated peritoneal dialysis Byonyks cycler and were evaluated for peritonitis over one year. Patients who had suffered peritonitis were followed up in OPD. Peritonitis episodes were documented and evaluated by sending dialysis effluent fluid in blood culture bottles for organism identification and sample for total leukocyte count as per ISPD guidelines. Each episode of peritonitis was managed as per ISPD guidelines. Results: The mean age of patients was 42.3 ± 13. Years and 50% were males. 49.9% were diabetics and 25% hypertensive. 4 episodes of peritonitis were observed in 3 patients, and not a single episode of exit site infection was observed. Calculated rate of peritonitis was 0.76 episode per patient year. Outcome: All peritonitis episodes resolved with antibiotics and no catheter removal was reported. Conclusion: This is the first report of peritonitis from Pakistan among patients undergoing APD. Only 4 episodes of peritonitis were observed that were easily managed with no consequences. Considering a new APD program the peritonitis rates were not significantly high and improvement in peritonitis rate is expected with gain of clinical experience in the future.